KEGIATAN SOSIALISASI PENGENALAN E-COMMERCE BERSAMA PANTI ASUHAN AL-HIKMAH PALEMBANG - Putra Ganda Dewata; Umi Karolina; Ambrosius Dwi Cahyadi; Reza Ardana; Maria Elana; Ery Hartati (Politeknik Negeri Sriwijaya, 2023)
The aim of the e-commerce introduction socialization is to familiarize children from the Al-Hikmah Orphanage with e-commerce as a digital solution for buying and selling, which offers more benefits and convenience compared to traditional trading activities. During this socialization, the children are provided with knowledge about what e-commerce is and taught basic skills to design simple product brochures using the Canva application. They are also introduced to the concept of digital marketing and provided with examples of its implementation. The socialization activities involve direct delivery of the material and interactive workshops, where the children are actively encouraged to interact with the Canva tools as part of the socialization process. The success of this socialization is reflected in the enthusiasm displayed by the children of the Al-Hikmah Orphanage, as they actively participate in the activities from start to finish. The objective of this socialization is to have a positive impact and enhance the children's knowledge about the benefits of e-commerce.